Chemoreactomic analysis of the drug prototype рilim-1 in comparison with zinc derivatives of nonsteroidal anti-inflammatory drugs - P. A. Galenko-Yaroshevsky; I. Y. Torshin; A. N. Gromov; I. A. Reyer; O. A. Gromova; B. A. Trofimov; L. N. Parshina; R. A. Murashko; O. V. Shelemekh; A. V. Zadorozhniy; V. L. Popkov; A. V. Zelenskaya; et al. (Фармакоэкономика)
Background. Gastroenterological side effects (esophageal, gastric, and intestinal erosions) with the use of drugs from the group of nonsteroidal anti-inflammatory drugs (NSAIDs) dictate the need to explore new candidate molecules with reduced ulcerogenic effects. The zinc-containing molecule-candidate рilim-1 may exert an anti-inflammatory effect and possibly improve the regenerative properties of the gastric mucosa.Objective: To explore the anti-inflammatory, ulcerogenic, analgentic and antivitamin effects of the рilim-1 molecule using cheomreactomics techniques.Material and methods. The chemoreactome assessment of the pharmacological properties of рilim-1 and zinc derivatives of known NSAIDs (ketorolac, diclofenac and nimesulide) was carried out using the methods of chemoinformation analysis of molecules developed at the scientific school of Academician Yu.I. Zhuravlev.Results. Pilim-1 has a distinct anti-inflammatory effect realized through modulation of cytokine activity, prostaglandin and leukotriene metabolism. The most important feature of the рilim-1 molecule is its neutrality with respect to vitamin metabolism, with comparability in potency of anti-inflammatory action to zinc-containing NSAID derivatives. The analgesic effect of рilim-1 is based on the inhibition of kinine and histamine receptors. The nociceptin receptor ORL1 can be inhibited by pilim-1 more effectively (IC50 198–214 nM) than zinc-NSAIDs (IC50 361–1093 nM). In the phenylquinone analgesia test in rats, pilim-1 demonstrated a slightly higher percentage of analgesia (44%; zinc-NSAIDs: 21–43%). The incidence of gastric ulcers at a dose of 100 mg/kg orally was estimated at 35% (other molecules - 75%). Compared with other zinc-derived NSAIDs, рilim-1 minimally interferes with vitamin and mineral metabolism.Conclusion. Chemoreactome analysis of рilim-1 indicates promising prospects for its application as an anti-inflammatory drug.